12. OUTCOMES OF INFERIOR TURBINOPLASTY FOR NASAL CONGESTION IN CHRONIC RHINOSINUSITIS PATIENTS WITH HYPERTROPHY OF INFERIOR TURBINATES (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate results of endoscopic inferior turbinoplasty for chronic rhinosinusitis patients with hypertrophy of inferior turbinates.Materials and methods: A prospective and case-by-case descriptive study with intervention on 39 patients who underwent endoscopic inferior turbinoplasty at 103 Military Hospital from November 2022 until January 2024.Results: Females accounted for 66.7% and males for 33.3%; Age average was 39.3 ± 6.4; All of patients had nasal congestion; Hypertrophy of inferior turbinates on both sides of the nose was mainly at level II, then at level III; Inferior turbinoplasty on both sides of the nose was 79.5%, and on one side was 20.5%. Propotion of NOSE average score pre-operatively was 85.6, post-operatively at 1-month and 3-month, which were 29.7 and 13.8; and VAS average score pre-operatively was 81.6, post-operatively at 1-month and 3-month, which were 42.2 and 20.2. The change between the two scales is statistically significant (p < 0.001).Conclusion: Endoscopic inferior turbinoplasty is the main surgery to improve the symptoms of nose congestion caused by hypertrophy of inferior turbinates.
Keywords: Inferior turbinate hypertrophy, endoscopic inferior turbinoplasty.